Preliminary Phytochemical and Anti-Arthritic Activity of an Ayurvedic Formulation -Yogaraja Gulgulu - Kumar and B.N. Vedha Hari3*, A. Puratchikody1, A.Yasodha2 A. Siva (Journal of Phytology, 2011)
Rheumatoid arthritis is a painful and crippling systemic disease for which there is no cure. Ayurveda is becoming popular with more and more people accepting its holistic approach to healing. The anti-arthritic activity of an ayurvedic formulation Yogaraja gulgulu was studied in rats. The formulation was then subjected for preliminary phytochemical studies and pharmacological investigation. The anti-arthritic activity was carried out by Fruend’s adjuant arthritis model. The ayurvedic formulation has exhibited significant anti-arthritic activity. The phytoconstituents screening reveals the presence of required component for anti-arthritic activity. The present study concludes that the yogaraja gulgulu can be used as anti-arthritic drug. Key words: Yogaraja gulgulu, arthritis, adjuant, indomethacin <span style="font-weight: normal; font-size: 7pt; line-height: 110%; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-variant: normal! important; mso-fareast-language: EN-SG; mso-font-kerning: 0pt; mso-no-proof: no; mso-ansi-language: EN-SG;" lang="EN-SG">A.Puratchikody et al. Preliminary Phytochemical and Anti-Arthritic Activity of an Ayurvedic Formulation -Yogaraja Gulgulu. J Phytol 3/3 (2011) 31-36.